The chase ebook - Kennedy, Elle (Briar U, 2018)
A sexy standalone novel from New York Times and international bestselling author Elle Kennedy! Everyone says opposites attract. And they must be right, because there's no logical reason why I'm so drawn to Colin Fitzgerald. I don't usually go for tattoo-covered, video-gaming, hockey-playing nerd-jocks who think I'm flighty and superficial. His narrow view of me is the first strike against him. It doesn't help that he's buddy-buddy with my brother. And that his best friend has a crush on me. And that I just moved in with them. Oh, did I not mention we're roommates? I suppose it doesn't matter. Fitzy has made it clear he's not interested in me, even though the sparks between us are liable to burn our house down. I'm not the kind of girl who chases after a man, though, and I'm not about to start. I've got my hands full dealing with a new school, a sleazy professor, and an uncertain future. So if my sexy brooding roomie wises up and realizes what he's missing? He knows where to find me.